Auger Electron Angular Distribution of Double Core-Hole States in the Molecular Reference Frame - Cryan, James P.; Glownia, J. M.; Andreasson, J.; Belkacem, A.; Berrah, N.; Blaga, C. I.; Bostedt, C.; Bozek, J.; Buth, C.; DiMauro, L. F.; Fang, L.; Gessner, O.; et al. (My University, 2010)
The Linac Coherent Light Source free electron laser is a source of high brightness x rays, 2×1011 photons in a ∼5 fs pulse, that can be focused to produce double core vacancies through rapid sequential ionization. This enables double core vacancy Auger electron spectroscopy, an entirely new way to study femtosecond chemical dynamics with Auger electrons that probe the local valence structure of molecules near a specific atomic core. Using 1.1 keV photons for sequential x-ray ionization of impulsively aligned molecular nitrogen, we observed a rich single-site double core vacancy Auger electron spectrum near 413 eV, in good agreement with ab initio calculations, and we measured the corresponding Auger electron angle dependence in the molecular frame.